Biodiversity values in environmental education research in the middle school context - Coito, Daniele Fabiane; Rink, Juliana (Revista Hipótese, 2019)
Biodiversity is a polysemous concept and involves several evaluative dimensions. Based on a state of the art research, we intend to discuss the values attributed to biodiversity, present in the Environmental Education academic research, involving Middle School, defended between 1981 and 2012. The analysis show a predominance dissertations defended in public institutions and concludes that the conceptual and instrumental values are predominant in relation to intrinsic and ethical / aesthetic values.